(untitled) (Global Journal of Medical Research, 2022)
The present article aims to investigate if there are differences -and which -between partner selection criteria of females in long term relationships that desire and that do not desire children with their current male partners. According to Evolutionary Psychology, these criteria are directly related to the type of parental investment practiced by the partner. The method consisted of virtual data collection of 288 answers to the research questionnaire aimed at cisgender, heterosexual and nulliparous women currently in a relationship, which evaluated the presence or absence of certain traits in their current male partners. Results showed significative differences between partner selection criteria of females that desired and that did not desire children in 14 male traits and no significative differences in the other 13 male traits presented. Traits containing significative differences were, whereas also culturally valued, mostly indicative of parental investment and genetic quality.